Analysis of Errors in Solving Hots Questions: A Study of Watson's Criteria Reviewed by Numerical Ability - Nisa, Fauziyatun; Setyaningsih, Nining (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
HOTS questions are designed as evaluation material to measure students' understanding and abilities in learning mathematics. However, the implementation of this concept is often hampered by the difficulties students face when solving these questions. The aim of this study is to examine the mistakes made by high school students in responding to HOTS questions, utilizing Watson's criteria and focusing on students' numerical abilities. The analysis of student mistakes involved utilizing Watson's error classifications, which encompass eight error indicators. This research includes qualitative descriptive research. Data was collected through written tests and interviews. The findings of the study reveal a notable association between errors and numerical proficiency in HOTS questions. A high numerical level has one of the eight Watson indicator errors, a medium numerical level has between two and four of the eight Watson criterion errors, and a low numerical level has more than 4 Watson criterion errors. The prevailing mistake made by students is the omitted conclusions, which is observed among students with high, moderate, and low numerical skills.The causes involve a lack of habit of writing conclusions, negligence, and rushing due to time constraints.